2004
DOI: 10.1073/pnas.0300619101
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of in vivo time-evolving neuroendocrine dose–response properties unveils admixed deterministic and stochastic elements

Abstract: Homeostasis in the intact organism is achieved implicitly by repeated incremental feedback (inhibitory) and feedforward (stimulatory) adjustments enforced via intermittent signal exchange. In separated systems, neurohormone signals act deterministically on target cells via quantifiable effector-response functions. On the other hand, in vivo interglandular signaling dynamics have not been estimable to date. Indeed, experimentally isolating components of an interactive network definitionally disrupts time-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 22 publications
3
73
0
Order By: Relevance
“…Details of the dynamic dose-response methodology were described in several earlier papers (11,16,17,18,19). The goal here was to relate time-varying ACTH concentrations (input, effector) to time-varying cortisol secretion rates (output, response) via both a classic fourparameter logistic dose-response function and a fiveparameter logistic dose-response function that contain two potencies to accommodate allowable (possible, but not obligatory) downregulation of ACTH drive.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the dynamic dose-response methodology were described in several earlier papers (11,16,17,18,19). The goal here was to relate time-varying ACTH concentrations (input, effector) to time-varying cortisol secretion rates (output, response) via both a classic fourparameter logistic dose-response function and a fiveparameter logistic dose-response function that contain two potencies to accommodate allowable (possible, but not obligatory) downregulation of ACTH drive.…”
Section: Methodsmentioning
confidence: 99%
“…Parameter sensitivity analyses showed that graded 1.33-, 1.77-, 3.16-, and 5.62-fold increases in t g,2 (the ED 50 or potency of GHS-induced drive of GHRH release) diminished GH peak height in the female, but not in the male, feedback construct (Table 4). Thus, in principle, either unequal GHS efficacy or unequal potency (ED 50 ) could heighten the basic sex difference in GHS action in vivo.…”
Section: Female-predominant Reduction In Gh Concentrations After Partmentioning
confidence: 99%
“…Specifically, the half-maximally inhibitory concentration of SRIF (t4 in the control function above) is varied by imposing random, zero-mean, unit-normalized Gaussian noise at a nominal 5% coefficient of variation (standard deviation/mean ϫ 100%) at 30-min intervals. Recent analyses indicate that endogenous stochastic inputs may modulate in vivo dose responsiveness in other neuroendocrine axes (50).…”
Section: General Formulation Of Core Equationsmentioning
confidence: 99%
“…The outcomes were basal (time-invariant), pulsatile (sum of secretory-burst mass) and total (sum of basal and pulsatile) GH secretion expressed in mg/l per 12 hours. The foregoing modifications are required for reliable conditional parameter estimation, as established more recently by statistical verification and experimental validation (31,32).…”
Section: Deconvolution Analysismentioning
confidence: 99%